Analisis Stock Split Berdasarkan Ukuran Perusahaan dan Market to Book Ratio Saham di Bursa Efek Indonesia - Cicilia Erna Susilawati; Rita Soehartono; Cyrillius Martono (Universitas Batanghari, 2022)
A stock split is a corporate action aimed at increasing trading liquidity. Where is carried out when the stock price is overvalued and reduces the ability of investors to buy the stock. The announcement of the stock split contains information that will be responded positively by investors. Company size and market to book ratio are company characteristics that can have an impact on investor response. Therefore, this study aims to analyze the difference in abnormal returns before and after the stock split by considering the size of the company and the market to book ratio. The research sample is a company that did a stock split in 2005-2019 with a total sample of 117 stocks. The results show that there is no difference in abnormal returns before and after the announcement of the stock split in companies with large and small sizes. However, there are differences in abnormal returns in medium-sized companies. Meanwhile, based on the market to book ratio, both companies with high and low market to book ratios have differences in abnormal returns before and after the announcement of the stock split.